PERAN GURU DALAM MEMBANGUN KARAKTER ENTREPRENEURSHIP ANAK MELALUI KEGIATAN MARKET DAY DI RA HARAPAN KITA: THE ROLE OF TEACHERS IN BUILDING CHILDREN'S ENTREPRENEURSHIP CHARACTER THROUGH MARKET DAY ACTIVITIES AT RA HARAPAN KITA - Munawarah, Munawarah; Ikhsan, Ikhsan; Santika, Santika; Ghafur, Muhammad (Thufuli, 2023)
Character development in children must be implemented from an early age. This includes building entrepreneurial character in children. Building entrepreneurial character in children requires stimulation in accordance with child development. Therefore it takes some efforts to implement it. This research was conducted at RA Harapan Kita, Kec. Lut Tawar, Kab. Central Aceh for teachers and children aged 5-6 years, with a total of 15 children. The research method uses qualitative methods with a descriptive approach. The data analysis technique uses the Milles and Huberman model, namely through observation, interviews and research-related literature studies. The results of the study show that the teacher's role in building entrepreneurial character in children can be done by providing stimulation through market day activities. It can be said that the implementation of market day activities went well as evidenced by the planning up to the activity evaluation stage. the benefits of implementing market day activities in shaping the character of entrepreneurs bring out the following characters. 1) have a sense of responsibility. 2) recognize self potential. 3) have a sense of responsibility. 4) creative. 5) able to solve problems.